Health education with adolescents sexuality and STI prevention (Research, Society and Development, 2020)
This is an experience report from a state public school in Niterói - RJ, where health education actions related to puberty and female and male anatomy were developed, in addition to themes related to sexuality, such as the prevention of sexually transmitted infections (STI) and pregnancy. Objective: describe the health promotion practice and sex education for high school students, based on knowledge of the collective health field. Method: qualitative-descriptive research, type of experience report. Resources such as lectures and slides, discussion wheels were used to help understand the contents. Conclusion: the dynamics contributed to the training of nursing students and understanding of the adolescents' view of knowledge of their bodies, and how they deal with sexuality. It was possible to understand the dynamic functions that the nurse must present when dealing with the community.